Phosphorylation of RNA Polymerase II by CDKC;2 Maintains the Arabidopsis Circadian Clock Period. (27th January 2022) - Uehara, Takahiro N; Nonoyama, Takashi; Taki, Kyomi; Kuwata, Keiko; Sato, Ayato; Fujimoto, Kazuhiro J; Hirota, Tsuyoshi; Matsuo, Hiromi; Maeda, Akari E; Ono, Azusa; Takahara, Tomoaki T; Tsutsui, Hiroki; et al.
Abstract: The circadian clock is an internal timekeeping system that governs about 24 h biological rhythms of a broad range of developmental and metabolic activities. The clocks in eukaryotes are thought to rely on lineage-specific transcriptional–translational feedback loops. However, the mechanisms underlying the basic transcriptional regulation events for clock function have not yet been fully explored. Here, through a combination of chemical biology and genetic approaches, we demonstrate that phosphorylation of RNA polymerase II by CYCLIN DEPENDENT KINASE C; 2 (CDKC;2) is required for maintaining the circadian period in Arabidopsis. Chemical screening identified BML-259, the inhibitor of mammalian CDK2/CDK5, as a compound lengthening the circadian period of Arabidopsis. Short-term BML-259 treatment resulted in decreased expression of most clock-associated genes. Development of a chemical probe followed by affinity proteomics revealed that BML-259 binds to CDKC;2. Loss-of-function mutations of cdkc;2 caused a long period phenotype. In vitro experiments demonstrated that the CDKC;2 immunocomplex phosphorylates the C-terminal domain of RNA polymerase II, and BML-259 inhibits this phosphorylation. Collectively, this study suggests that transcriptional activity maintained by CDKC;2 is required for proper period length, which is an essential feature of the circadian clock in Arabidopsis.